The COVID-19 pandemic and global environmental change: Emerging research needs. (January 2021) - Barouki, Robert; Kogevinas, Manolis; Audouze, Karine; Belesova, Kristine; Bergman, Ake; Birnbaum, Linda; Boekhold, Sandra; Denys, Sebastien; Desseille, Celine; Drakvik, Elina; Frumkin, Howard; Garric, Jeanne; et al.
Highlights: Environmental conditions influence the emergence and spread of SARS-CoV-2. The contribution of climate and air pollution requires additional studies. Environmental stressors may contribute to the severity of COVID-19. Behavioural and societal changes may remain long after the pandemic. COVID-19 will have a long-lasting impact on the environmental health field. Abstract: The outbreak of COVID-19 raised numerous questions on the interactions between the occurrence of new infections, the environment, climate and health. The European Union requested the H2020 HERA project which aims at setting priorities in research on environment, climate and health, to identify relevant research needs regarding Covid-19. The emergence and spread of SARS-CoV-2 appears to be related to urbanization, habitat destruction, live animal trade, intensive livestock farming and global travel. The contribution of climate and air pollution requires additional studies. Importantly, the severity of COVID-19 depends on the interactions between the viral infection, ageing and chronic diseases such as metabolic, respiratory and cardiovascular diseases and obesity which are themselves influenced by environmental stressors. The mechanisms of these interactions deserve additional scrutiny. Both the pandemic and the social response to the disease have elicited an array of behavioural and societal changes that may remain long after the pandemic and that may have long term health effects including on mental health. Recovery plans are currently being discussed or implemented and the environmental and health impacts of those plans are not clearly foreseen. Clearly, COVID-19 will have a long-lasting impact on the environmental health field and will open new research perspectives and policy needs.